Identification of In Vitro Bioavailability of Zinc in Different Types of Eggs and Methods of Processing - . Rimbawan; Cesilia Meti Dwiriani; Ennita Fahriza (Media Gizi dan Keluarga, 2000)
This research was intended to asssess zinc content and zinc bioavailability from six kinds of egg processing (boiled, poached, salted, fried egg with shallow frying (Ã¢â‚¬Å“dadarÃ¢â‚¬Â and Ã¢â‚¬Å“ceplokÃ¢â‚¬Â), also Ã¢â‚¬Å“pindangÃ¢â‚¬Â on three types of egg (local hens egg, layer egg and ducks egg). An in vitro dialysis procedure was employed to determine zinc bioavailablity. The experimental design used was complete random design with factorial experimental and further statistical analysis by Duncan Multiple Range. The results indicated that zinc bioavailabilities from three types of egg with six kinds of egg processing were ranged from 3.60 to 19.01 percents. Zinc content was ranged from 1.15 to 3.12 mg/100 g in wet basis or 2.59 to 12.22 mg/100 g in dry basis. Frying egg decreased zinc bioavailability and zinc content significantly (p<0.05). Boiling and poaching of egg increased zinc bioavailability and zinc content significantly (p<0.05). The data suggest that chickens egg (local henÃ¢â‚¬â„¢s and layer egg) processed by boiling and poaching increased zinc bioavailability.